1993
DOI: 10.1148/radiology.186.2.8421757
|View full text |Cite
|
Sign up to set email alerts
|

Normal uterus and FIGO stage I endometrial carcinoma: dynamic gadolinium-enhanced MR imaging.

Abstract: Dynamic magnetic resonance (MR) imaging was performed on a 1.5-T superconducting unit for evaluation of 26 stage I endometrial carcinomas. To establish the appearance of the normal uterus, 27 normal uteri were also evaluated. After rapid injection of gadopentetate dimeglumine, dynamic images were obtained every 30 seconds with the spin-echo technique in the sagittal plane. On dynamic studies of endometrial carcinoma, the tumor-myometrial contrast was marked at 120 seconds after administration of gadopentetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
94
1
12

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(113 citation statements)
references
References 0 publications
6
94
1
12
Order By: Relevance
“…Our results are in keeping with previous series (Hardesty et al 2000;Yamashita et al 1993;Ito et al 1994). We obtained an accuracy of 95% in the evaluation of deep myometrial invasion and an accuracy of 88% regarding cervical extension.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in keeping with previous series (Hardesty et al 2000;Yamashita et al 1993;Ito et al 1994). We obtained an accuracy of 95% in the evaluation of deep myometrial invasion and an accuracy of 88% regarding cervical extension.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of local extension, the reported rate of accurate diagnosis of myometrial invasion is 58 77 [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a contrast dynamic study is highly effective, improving accuracy signi cantly from 58 77 with T2-enhanced images alone to 85 93 [21][22][23][24] . However, despite this improvement, it is believed that allergies to contrast agents and the fact that contrast agents cannot be used in patients with compromised renal function will mean that, in the future, it will become more important to implement presurgical diagnosis of endometrial cancer using non-contrast MRI, along with diagnosing localized extension prior to surgery using basic MRI technology.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no consensus in the literature regarding the added value of DCE-MRI in staging of endometrial cancer. Although the majority of the published studies demonstrate that the addition of multiphase DCE-MRI to T2W imaging leads to a significant improvement in the accuracy of assessment of the deep myometrial invasion [8,9,[11][12][13][14][15], some authors have found no significant difference [16,17].…”
mentioning
confidence: 99%